Sleep quality and its relationship with night eating syndrome, the risk of diabetes, and nutritional status among university students - Akdevelioğlu, Yasemin; Şahin, Teslime Özge; Yesildemir, Ozge (Progress in Nutrition, 2020)
Changes in sleep quality increase the risk of diabetes and obesity by affecting nutrition. Thisstudy was conducted to find the correlation between sleep quality and night eating syndrome in addition toobesity predisposition and the risk of diabetes. 550 university students including 330 women and 220 menbetween the ages of 17-42 years participated in the study. A face to face questionnaire was conducted in orderto collect information about their personal characteristics, nutritional habits, and physical activities. Theiranthropometric measurements were taken and food consumption in the last 24 hours were recorded. TheNight Eating Syndrome Questionnaire, the Pittsburg Sleep Quality Index, and the Finnish Diabetes RiskScore were conducted on the participants. 40% of the students were found to have good sleep quality, while60% were found to have poor sleep quality. The median values of night eating syndrome, the risk of diabetes,and the sleep quality scores of participants with good sleep quality were significantly lower than that of theparticipants with poor sleep quality. Also, a positive correlation was found between the sleep quality scorealong with the night eating and diabetes risk scores. Moreover, night eating syndrome and sleep duration werepositively correlated with waist circumference and waist/height ratio which are indicators of obesity. As a result,the study found that poor sleep quality increased night eating syndrome, obesity predisposition, and therisk of diabetes, a metabolic disease. University students may be recommended to improve their sleep qualityin order to prevent the above-mentioned metabolic diseases.